2022
DOI: 10.1111/jfd.13699
|View full text |Cite
|
Sign up to set email alerts
|

Immersion challenge model for Flavobacterium psychrophilum infection of Atlantic salmon (Salmo salar L.) fry

Abstract: Flavobacterium psychrophilum is the causative agent of bacterial cold‐water disease (CWBD) and rainbow trout fry syndrome (RTFS), which affect salmonids. To better understand this pathogen and its interaction with the host during infection, including to support the development of resistant breeds and new vaccines and treatments, there is a pressing need for reliable and reproducible immersion challenge models that more closely mimic natural routes of infection. The aim of this present study was to evaluate a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…As previously indicated, the challenge results were at times contradictory. In Atlantic salmon, using the immersion challenge method and a dose >10 6 CFU/mL to replicate the clinical signs, Macchia et al (2022) reported a less than 20% accumulated mortality. By contrast, Hoare et al (2019) used isolate AVU‐3S/13 serotype Fp T (type 0) in Atlantic salmon, with accumulated mortalities of 70% at an inoculation dose of 4 × 10 7 CFU/fish by intramuscular inoculation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously indicated, the challenge results were at times contradictory. In Atlantic salmon, using the immersion challenge method and a dose >10 6 CFU/mL to replicate the clinical signs, Macchia et al (2022) reported a less than 20% accumulated mortality. By contrast, Hoare et al (2019) used isolate AVU‐3S/13 serotype Fp T (type 0) in Atlantic salmon, with accumulated mortalities of 70% at an inoculation dose of 4 × 10 7 CFU/fish by intramuscular inoculation.…”
Section: Resultsmentioning
confidence: 99%
“…6 CFU/mL to replicate the clinical signs,Macchia et al (2022) reported a less than 20% accumulated mortality. By contrast,Hoare et al (2019) used isolate AVU-3S/13 serotype Fp T (type 0) in Atlantic salmon, with accumulated mortalities of 70% at an inoculation dose of 4 × 10 7 CFU/fish by intramuscular inoculation.Dead fish showed scale loss, skin lesions such as ulcers and/or eroded fins.…”
mentioning
confidence: 95%
“…Previous virulence studies addressing the question of F. psychrophilum host specificity focused on a few strains tested in several fish species [ 24 , 26 , 39 42 ] or on a single host challenged with isolates retrieved from various fish species [ 23 , 25 , 42 , 43 ]. However, the limited number of strains tested in each study and the lack of data regarding their genotype make comparisons difficult.…”
Section: Discussionmentioning
confidence: 99%
“…F. covae typically affects the gills, the skin, and fins [ 3 ]. Thus, the challenge by immersion is closer to the natural route of infection [ 30 ]. Mortalities were recorded daily for 2 weeks in each group to calculate the percent survival and to assess the protective effect of the vaccination.…”
Section: Methodsmentioning
confidence: 99%